Interferometric scattering microscopy - Ginsberg, Naomi S.; Hsieh, Chia Lung; Kukura, Philipp; Piliarik, Marek; Sandoghdar, Vahid (Nature Reviews Methods Primers, 2025)
Over the past two decades, interferometric scattering (iSCAT) microscopy has become a powerful label-free imaging method with a range of applications in fundamental science and technology. iSCAT detects the scattering of subwavelength entities through interference with a reference beam of light. Performed in a variety of illumination and detection schemes, iSCAT has exploited both amplitude and phase information to reach single-molecule detection sensitivity; to determine the size, mass and refractive index of nanoparticles; to achieve high spatiotemporal precision in 3D tracking of nanoparticles; to image subcellular nanostructures; and to quantify ultrafast diffusion and transport of energy in solids. In this Primer, we describe the basic principles of iSCAT detection and imaging from theoretical and practical points of view. We discuss various factors that affect the attainable signal-to-noise ratio, which in turn determines crucial performance features such as sensitivity and speed. We survey selected applications in which iSCAT has been instrumental in providing new insights. Finally, we discuss some of the current challenges and potential avenues for advancing the technique further.
CRIS-Team Scopus Importer:2025-05-02